Bridging Skills and Language: Developing Web-Based English Learning Platforms for Vocational Education - Ahmad Rossydi; Peter John Wanner; Muawal Al As’ary; Benny Kurnianto; Aat Eska Fahmadi (International Journal of Language Education, 2026)
This research is based on the rapid development of Information and Communication Technology (ICT) in the education sector. Developing a web-based English learning platform tailored to vocational students not only meets the demand for innovative educational solutions but also improves their language competence and prepares them for the job market. It also promotes access, scalability, 21st-century skills, and real-life issues, and helps shape what a modern, accessible, 21st-century education is like. This study aims to contribute to addressing the increasingly widespread demand for ICT integration in education, especially in vocational higher education, and to reconcile technology with human resource development. The study's objective was to develop a web-based learning platform, "Gamal Station," focused on English language instruction for vocational students. The study employed a Design and Development (D&D) research approach, following a structured analysis, design, and development method. The resulting product, Gamal Station, offers features for learning English, including content, exercises, and assessments that can be accessed anytime, anywhere. Expert validation of both the material and the media verified the tool's effectiveness and usability, classifying it as a suitable educational resource. Nevertheless, some minor challenges, such as network limitations and necessary interface modifications, were noted during the evaluation. The application demonstrated significant potential to enhance English teaching and learning outcomes following adjustments. This research highlights the need to employ innovative, accessible educational tools in vocational training to meet diverse learner needs and support contemporary teaching methods. The affirmation of Gamal Station represents progress in the creation of ICT-based educational resources, setting the stage for broader adoption in vocational institutions and encouraging more inclusive and effective English language instruction.